Clinical and Histopathological Diagnosis of Glomus Tumor: An Institutional Experience of 138 Cases. (May 2015) - Mravic, Marco; LaChaud, Gregory; Nguyen, Alan; Scott, Michelle A.; Dry, Sarah M.; James, Aaron W.
Background . Glomus tumors are relatively uncommon subcentimeteric benign perivascular neoplasms usually located on the fingers. With their blue-red color and common subungual location, they are commonly confused for vascular or melanocytic lesions. To date there is no comprehensive review of an institutional experience with glomus tumors. Methods . A 14-year retrospective review of all cases within University of California, Los Angeles, with either a clinical or pathological diagnosis of glomus tumor was performed. Data obtained included demographic information, tumor description, pathological diagnoses, immunohistochemical studies, radiographic and treatment information, and clinical course. Rates of concordance between clinical and pathological diagnoses and an evaluation of overlap with other entities were assessed. Results . Clinical diagnosis of glomus tumor showed concordance with a histopathological diagnosis (45.4% of cases). The most common alternate clinical diagnoses included lipoma, cyst, or angioma. A pathological diagnosis of glomus tumor was most common in the fourth to seventh decades of life. The most common presentation was a subcentimeter lesion on the digit. Deep-seated tumors had a strikingly increased risk for malignancy (33%). Radiological studies were not relied on frequently (18.2% of cases). Immunohistochemical analysis showed diffuse αSMA and MSA expression in nearly all cases (99% and 95%, respectively), with focal to diffuse CD34 immunostaining in 32% of cases. Discussion . Our study illustrates trends in the clinical versus pathologic diagnoses of glomus tumor, common competing diagnoses, a difference in demographics than is commonly reported (older age groups most commonly affected), and important differences in the use adjunctive diagnostic tools including radiology and immunohistochemistry.